Transformasi Limbah Plastik Menjadi Fiber Polyester: Strategi Pengurangan Pencemaran Lingkungan dan Peningkatan Ekonomi Desa Sumberdem, Kabupaten Malang - Irawan, Dani; Sutadji, Eddy; Suharmanto, Suharmanto; Annisya, Annisya; Pratama, Muhammad Yandi; Yuniar, Mirza (Abdimas Indonesian Journal, 2024)
Waste that has not been handled properly is located in Sumberdem Village, Malang Regency. Waste processing has so far been carried out by separating organic and inorganic waste. Organic waste is processed into compost because it is easily decomposed and can help fertilize the soil, such as use in coffee plantations. The problem is inorganic waste in the form of plastic that is not utilized properly. So far, plastic waste has been dumped on riverbanks and burned so that it causes new problems, namely environmental pollution from the smoke from burning. Based on the problems that have been identified by the community service team, the solutions offered are: (1) Creating appropriate technology in the form of a rotary type plastic pet pelletizer machine, (2) Workshop on the Application of Appropriate Technology (TTG). The method used in this community service activity is community empowerment which is carried out through training and knowledge transfer. The results of this activity are (1) Development of appropriate technology in the form of a Rotary Type Plastic PET Pelletizer machine has been proven effective in processing plastic waste into polyester fiber plastic pellets, (2) Through technical guidance on the use of the Rotary Type Plastic PET Pelletizer machine, waste recycling business actors can operate the machine better and more efficiently.